Education in Mexico and technological public policy for developing complex thinking in the digital era: A model for technology management - Berenice Alfaro-Ponce; Mariel Alfaro-Ponce; Cristopher A. Mu\~noz-Ibá\~nez; Rosa E. Durán-González; Jorge C. Sanabria-Zepeda; Zaira L. González-Gómez (Journal of Innovation & Knowledge (JIK), 2023)
Currently, numerous studies highlight the importance of technology as an effective resource for improving the quality of education. Like other countries in the region, Mexico greatly emphasizes improving its education system comprehensively and competitively, and technology has become a fundamental strategy to achieve this goal. Technology has allowed it to fill existing gaps and introduce innovative models in the digital age, promoting human capital development and fostering thriving communities. Technology also facilitates the development of competencies, such as complex thinking and the skills required to utilize Education 4.0 resources. However, these advances are at risk without examining the possibilities for technology transfer in the region's educational institutions. Accordingly, the following questions arise: a) What is the probability of achieving technology transfer to primary education institutions; b) What investments or modifications are necessary in the existing infrastructure to transfer educational and other technologies? We aimed to develop a quantitative data analysis model to examine the capacity of primary education institutions, applicable also to higher education, to adapt, assimilate, and transfer technology to improve educational quality in Mexico, as proposed by González Sabater in 2011. The results suggest the feasibility of a technology management system validated through a reliable database, considering the existing infrastructure as a basis for technology transfer. This research is relevant in establishing the probability of success of an educational institution in completing the process of assimilation and technology transfer, thus also contributing to governmental decision-making on educational spending.
Keywords: 650; Basic education; Educational innovation; Higher education; Complex thinking; Technology management